TECHNOLOGY OF FORMATION OF STUDENTS’ MOTIVATIONAL WILLINGNESS FOR PROFESSIONAL ACTIVITY - M.G, Sergeeva; I.V, Okhotnikov; Ju.V., Panko; L.A., Shvedov; D.M., Kasymova; M.N, Zolotova (Gênero & Direito, 2019)
The process of formation of the professional personality begins from the moment of choosing a profession and lasts throughout the professional life of a person, during which the most important problems of the relationship between a person and a profession are revealed. In psychology and pedagogy of Western countries, the problem of incentives to activity is revealed in a number of concepts and theories from different positions. Currently, motivation as a mental phenomenon is interpreted in different ways. The main theories of motivation should be divided into two directions: substantive theories, which consider motivation from structural positions, and procedural theories, which consider motivation as a dynamic formation. What unites these areas is the understanding of motivation as secondary to the motive of education. The concept of “willingness” for activity is considered as an active and effective state of the person, the installation to determine behavior, mobilization of forces to perform the task. In the structure of professional willingness of the individual, researchers identify different components, among which the most important is the motivational one –attitude to the profession, the need to solve successfully the task and interest in the activity. An essential component of professional willingness is psychological willingness, which should be considered as a complex functional-psychological and personal formation, including: a positive attitude to a particular type of activity; adequate character traits and temperament to the requirements of the activity; the necessary knowledge, skills, abilities, and habits; stable professionally important features of cognitive and emotional-volitional processes.